2017
DOI: 10.1016/j.addbeh.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Now is the time to advocate for interventions designed specifically to prevent and control waterpipe tobacco smoking

Abstract: Waterpipe tobacco usage is spreading rapidly worldwide, with reports of more youth being waterpipe users compared to adults. In many areas of the world, waterpipe usage surpasses cigarette smoking. Waterpipes and cigarettes are both mechanisms for inhalation of tobacco smoke and therefore have serious health consequences. However, because of the many differences between the two products, prevention and control strategies that have proven effective for cigarettes may not transfer readily to waterpipe. This repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 77 publications
(101 reference statements)
0
49
0
2
Order By: Relevance
“…Many adolescents perceive waterpipe use as less harmful than other tobacco products (Akl et al, 2015), therefore it is plausible to regard waterpipe as the second step in the desensitization process. Waterpipe and e-cigarettes share appealing perceptual components such as tempting flavors and smells, sight of the voluminous exhaled smoke or vapor, and the visual and tactile sensations of the device (Lopez et al, 2017; Patrick et al, 2016; Soule, Rosas, & Nasim, 2016) which may explain our findings that both e-cigarette and waterpipe use can serve as interchangeable initiator product for future alternative and/or conventional cigarette use.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Many adolescents perceive waterpipe use as less harmful than other tobacco products (Akl et al, 2015), therefore it is plausible to regard waterpipe as the second step in the desensitization process. Waterpipe and e-cigarettes share appealing perceptual components such as tempting flavors and smells, sight of the voluminous exhaled smoke or vapor, and the visual and tactile sensations of the device (Lopez et al, 2017; Patrick et al, 2016; Soule, Rosas, & Nasim, 2016) which may explain our findings that both e-cigarette and waterpipe use can serve as interchangeable initiator product for future alternative and/or conventional cigarette use.…”
Section: Discussionmentioning
confidence: 70%
“…This finding highlights the importance of developing tailored programs to prevent their use on the increasingly diverse tobacco market. Evidence-based interventions to prevent youth tobacco smoking should pay more attention to waterpipe use prevention and start incorporating e-cigarette and vaporizer use prevention (Lopez et al, 2017; U.S.DHHS, 2016). School-based tobacco interventions should be expanded with messages targeting e-cigarette and waterpipe prevention, specifically educating youth about the adverse health effects of vaping substances from e-cigarettes including nicotine as an addictive substance, flavoring chemicals and other toxicants (Gorukanti et al, 2017; Miech et al, 2017; Pepper et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with research showing that young adults perceive hookah as less addictive and easier to quit than tobacco cigarettes (Akl et al, 2015). Importantly research indicates that the amount of smoke inhaled during a 30–60 minute hookah session can equal that produced by 100 or more cigarettes (Maziak et al, 2008), and long-term hookah use is associated with the development of cancer, cardiovascular disease, and decreased pulmonary functioning (Lopez, Eissenberg, Jaafar, & Afifi, 2017). Moreover, there are 54 case reports in the medical literature of acute carbon monoxide (CO) poisoning related to hookah smoking, suggesting that hookah likely poses acute risks for pregnant women as such high quantities of CO would be particularly harmful during pregnancy (Retzky, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The increases in waterpipe use could be due to several factors, including social acceptance, use of flavored tobacco, and the misconception that waterpipe filters the smoke from toxic compounds [6, 7]. Therefore, providing science-based evidence of the health effects of waterpipe smoke might contribute to overcoming the spread of this form of smoking [8, 9]. Previous literature has shown that, similar to cigarette smoking, WTS is likely associated with cardiovascular and lung diseases as well as cancer [10-13].…”
Section: Introductionmentioning
confidence: 99%